EXPLORING NEW FEATURES FOR THE PERTURBED CHEN-LEE-LIU MODEL VIA (m - Bulut, Hasan; Ismael, Hajar F. (Inst Mathematics & Mechanics, Natl Acad Sciences Azerbaijan, 2022)
In this work, the perturbed Chen-Lee-Liu equation, which describes the propagation of an optical pulse in plasma and optical fiber is studied. The (m + G/')-expansion method is used for this purpose. As a result, bright-singular, dark-singular, dark and periodic optical soliton waves are constructed. Specific values for the parameters under conditions are also provided to display the pulse propagation of the found solutions.
Keywords: Chen-Lee-Liu equation; analytical method; Exact solutions